The Pelabon Munitions works and the Belgian village on the Thames: community and forgetfulness in outer-metropolitan suburbs. Issue 2 (3rd May 2016) - Declercq, Christophe; Baker, Helen
Abstract: West of London in Richmond and Twickenham, 6000 Belgian refugees developed a flourishing social life, drawn in the context of the national 'shell crisis' by employment opportunities at the Pelabon Munitions Works. This article asks why Belgian community life was richer here than almost anywhere else, and explores the significance of refugees' social interaction for their class and other group identities. Finally, the article seeks to explain why this vast community became completely forgotten locally.